Correlation of Morphology with Photocurrent Generation in a Polymer Blend Photovoltaic Device. Issue 9 (30th January 2014) - Ostrowski, David P.; Vanden Bout, David A.
<x xml:space="preserve">Abstract</x> Morphological effects on photovoltaic (PV) properties are studied through scanning photocurrent (PC) and photoluminescence (PL) microscopy of a solution processed, polymer blend PV device composed of PFB [poly(9, 9′‐dioctylfluorene‐co‐bis‐N, N‐(4‐butylphenyl)‐bis‐N, N‐phenyl‐1, 4‐phenylenediamine] and F8BT [poly(9, 9′‐dioctylfluorene‐co‐benzothiadiazole]. As PFB and F8BT have unique absorbance bands, it is possible to selectively excite only F8BT (488 nm) or both PFB and F8BT (408 nm). Local voltage‐dependent photocurrent (LVPC) measurements from particular regions of interest in the PV show that the diode characteristics between different morphologies are essentially the same, except in regard to the magnitude of PC generated. A local PL spectrum is measured simultaneously with PC generation at each pixel in the image maps. Through integration of the local PL spectrum over particular wavelength ranges, PL image maps are created of PFB‐PL (435 to 475 nm), F8BT‐PL (530 to 570 nm), exciplex‐PL (620 to 685 nm) and total‐PL (entire spectrum). These data allow direct correlation of PC generation with local chemical composition variations within the PV device. PL image maps show morphological variations on the order of 0.5 to 1 µm of alternating PFB‐rich and F8BT‐rich phases. While illuminating only F8BT (488 nm light), the PFB‐rich phases produce the most PC, however, while illuminating both polymers but mostly PFB (408 nm light), the F8BT‐rich phases produce the most PC. These results show that in the morphology where the light absorbing material is less concentrated, the PC generation is increased. Additionally, the exciplex‐PL is found to not be a significant radiative loss mechanism of charge carriers for PC generation.